Studi Orientasi Pasar dan Inovasi Produk Terhadap Kinerja Pemasaran UMKM di Kabupaten Indramayu - Nurpratama, Meddy; Sonjaya, Nana Supriatna; Yudianto, Agus; Agung, Ismail (Jurnal EMT KITA, 2024)
This study aims to determine the influence of market orientation and product innovation on the marketing performance of MSMEs in Indramayu Regency. The method used in this research is multiple linear regression analysis. Data were obtained through the distribution of questionnaires to respondents who are MSME actors in Indramayu. Data analysis was conducted using multiple linear regression techniques to identify the relationship between independent and dependent variables. Additionally, this study uses Pearson correlation to examine the relationship between market orientation and product innovation with marketing performance. The results of the study show that both market orientation and product innovation have a significant and positive influence on the marketing performance of MSMEs. These findings emphasize the importance for MSMEs to integrate market orientation and product innovation into their marketing strategies to enhance marketing effectiveness and efficiency, and support business growth